2011
DOI: 10.1038/bjc.2011.37
|View full text |Cite|
|
Sign up to set email alerts
|

Farnesoid X receptor, overexpressed in pancreatic cancer with lymph node metastasis promotes cell migration and invasion

Abstract: Background:Lymph node metastasis is one of the most important adverse prognostic factors for pancreatic cancer. The aim of this study was to identify novel lymphatic metastasis-associated markers and therapeutic targets for pancreatic cancer.Methods:DNA microarray study was carried out to identify genes differentially expressed between 17 pancreatic cancer tissues with lymph node metastasis and 17 pancreatic cancer tissues without lymph node metastasis. The microarray results were validated by real-time PCR. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 40 publications
5
59
0
Order By: Relevance
“…However, the expression of FXR and its role in the tumorigenesis remain controversial. Lee et al (11) reported that FXR overexpression in pancreatic cancer tissues with lymphatic metastasis was associated with poor patient survival, and downregulation of FXR was an effective approach for inhibition of pancreatic tumor progression. However, for other cancers, FXR was considered as a tumor suppressor rather than a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of FXR and its role in the tumorigenesis remain controversial. Lee et al (11) reported that FXR overexpression in pancreatic cancer tissues with lymphatic metastasis was associated with poor patient survival, and downregulation of FXR was an effective approach for inhibition of pancreatic tumor progression. However, for other cancers, FXR was considered as a tumor suppressor rather than a tumor promoter.…”
Section: Discussionmentioning
confidence: 99%
“…14 In contrast, the inhibition of FXR promotes apoptosis in Barrett's esophageal-derived cells 15 and inhibits proliferation, migration and invasion in pancreatic cancer cells. 16 In our previous study, we have demonstrated that FXR is expressed in tissues of normal and tumor Fisher rat testis and in Leydig normal and tumor cell lines. 17 Particularly, in R2C rat Leydig tumor cells the FXR activators CDCA and GW4064 downregulate aromatase expression at both mRNA and protein levels, together with the inhibition of its enzymatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous genome-wide studies aimed at identifying the transcriptional mechanisms that underlie metastasis formation have primarily focused on comparisons between end-stage primary and metastatic tumors of mouse or human origin [20, 26], broad characterization of transcriptional changes [27], or between primary tumors of differing metastatic phenotypes [2830]. In particular, experiments using in vivo selection of metastatic cell lines have yielded considerable insight into the transcriptional basis for metastatic localization [3133].…”
Section: Discussionmentioning
confidence: 99%